2011
DOI: 10.1590/s1516-80342011000400016
|View full text |Cite
|
Sign up to set email alerts
|

Zumbido no trabalhador exposto ao ruído

Abstract: OBJETIVO: Verificar as características, prevalência e repercussão do zumbido em trabalhadores expostos ao ruído. MÉTODOS: Um total de 585 trabalhadores de uma indústria alimentícia foi questionado sobre zumbido. Aqueles que referiram zumbido por mais de cinco minutos e há mais de seis meses responderam à entrevista abordando histórico ocupacional e do zumbido, responderam ao questionário Tinnitus Handicap Inventory, e realizaram audiometria tonal. Foi realizada análise estatística dos dados. RESULTADOS: Foi en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
1
8
0
3
Order By: Relevance
“…A study has shown that physicians believe that 50% of the individuals complaining of tinnitus improve their clinical conditions with reduced caffeine intake. 43 Regarding previous disease history, head traumas, cardiac disorders, diabetes and high cholesterol, high blood pressure, and migraines were reported; the latter two retaining the highest occurrences in the sample. The possibility of occurrence of these various factors and the probable interaction between them encumbers determining the cause of tinnitus.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…A study has shown that physicians believe that 50% of the individuals complaining of tinnitus improve their clinical conditions with reduced caffeine intake. 43 Regarding previous disease history, head traumas, cardiac disorders, diabetes and high cholesterol, high blood pressure, and migraines were reported; the latter two retaining the highest occurrences in the sample. The possibility of occurrence of these various factors and the probable interaction between them encumbers determining the cause of tinnitus.…”
Section: Discussionmentioning
confidence: 93%
“…The possibility of occurrence of these various factors and the probable interaction between them encumbers determining the cause of tinnitus. 43 Regarding medication use, 52.7% of the individuals took some type of drug, and 26.3% reported having used tinnitus relief medication. A recent study stated that pharmacotherapy can trigger or aggravate vestibular symptoms such as vertigo, tinnitus, and dizziness in the elderly, and attention and caution are therefore required in medication prescription in this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hearing problems more often affect males. According to some studies 3,15,[20][21][22][23] , this susceptibility related to male gender for hearing problems may be explained due to the protective functions of estrogens in women, considering estradiol is an important regulator of hearing in females 15 .…”
Section: Discussionmentioning
confidence: 99%
“…A prevalência de diagnóstico de zumbido na população estudada foi de 13,3%, com forte significância estatística, sendo superior à encontrada (7,2%) no grupo da indústria alimentícia 25 , e inferior à encontrada (23,6%) no grupo de policiais do trânsito rodoviário 20 . A exposição constante ao ruído aumenta o risco de desenvolvimento de zumbido 10 .…”
Section: Discussionunclassified